A Question on Polynomials, part 4

Algebra Level 4

Given that f f is a polynomial of degree 3 and that f ( k ) = 3 k f(k)=3^k for k = 1 , 2 , 3 , 4 k=1, 2, 3, 4 .

Find the value of f ( 5 ) f(5) .


The answer is 195.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Brian Moehring
Jul 29, 2018

Since the x x -values are consecutive, we can just consider the triangle of differences: Row 0 3 3 2 3 3 3 4 Row 1 6 18 54 Row 2 12 36 Row 3 24 \begin{array}{lcccccccc} \text{Row 0} & & 3 & & 3^2 & & 3^3 & & 3^4 \\ \text{Row 1} & & & 6 & & 18 & & 54 & \\ \text{Row 2} & & & & 12 & & 36 & & \\ \text{Row 3} & & & & & 24 & & & \end{array}

And since the interpolating polynomial has degree 3 3 , all the rows below Row 3 are zero. This gives the next value by working from the bottom and moving up the triangle Row 0 3 3 2 3 3 3 4 195 Row 1 6 18 54 114 Row 2 12 36 60 Row 3 24 24 Row 4 0 \begin{array}{lcccccccccc} \text{Row 0} & & 3 & & 3^2 & & 3^3 & & 3^4 & & \color{#3D99F6}{195}\\ \text{Row 1} & & & 6 & & 18 & & 54 & & \color{#3D99F6}{114} & \\ \text{Row 2} & & & & 12 & & 36 & & \color{#3D99F6}{60} & & \\ \text{Row 3} & & & & & 24 & & \color{#3D99F6}{24} & & & \\ \color{#3D99F6}{\text{Row 4}} & & & & & & \color{#3D99F6}{0} & & & & \end{array}

which gives f ( 5 ) = 195 f(5) = \boxed{195} .


Clarification:

  • To move down the triangle, at each step we use a b b a \begin{array}{ccc} a & & b \\ & \color{#3D99F6}{b-a} & \end{array}
  • To move up the triangle, at each step we use a a + b b \begin{array}{ccc} a & & \color{#3D99F6}{a+b} \\ & b & \end{array}
  • We can also read off the polynomial from the left-most side of the triangle as f ( x ) = 3 0 ! + 6 1 ! ( x 1 ) + 12 2 ! ( x 1 ) ( x 2 ) + 24 3 ! ( x 1 ) ( x 2 ) ( x 3 ) f(x) = \frac{3}{0!} + \frac{6}{1!}(x-1) + \frac{12}{2!}(x-1)(x-2) + \frac{24}{3!}(x-1)(x-2)(x-3) and we could do similarly even if the x x -values aren't consecutive, but then we'd have to use Newton's divided differences instead.

For variety, I am using matrix to solve the problem.

Let f ( x ) = a x 3 + b x 2 + c x + d f(x) = ax^3+bx^2+cx+d . Then we have:

[ 1 1 1 1 8 4 2 1 27 9 3 1 64 16 4 1 ] [ a b c d ] = [ 3 9 27 81 ] \begin{bmatrix} 1 & 1 & 1 & 1 \\ 8 & 4 & 2 & 1 \\ 27 & 9 & 3 & 1 \\ 64 & 16 & 4 & 1 \end{bmatrix} \begin{bmatrix} a \\ b \\ c \\ d \end{bmatrix} = \begin{bmatrix} 3 \\ 9 \\ 27 \\ 81 \end{bmatrix}

[ a b c d ] = [ 1 1 1 1 8 4 2 1 27 9 3 1 64 16 4 1 ] 1 [ 3 9 27 81 ] = [ 1 6 1 2 1 2 1 6 3 2 4 7 2 1 13 3 19 2 7 11 6 4 6 4 1 ] [ 3 9 27 81 ] = [ 4 18 32 15 ] \implies \begin{bmatrix} a \\ b \\ c \\ d \end{bmatrix} = \begin{bmatrix} 1 & 1 & 1 & 1 \\ 8 & 4 & 2 & 1 \\ 27 & 9 & 3 & 1 \\ 64 & 16 & 4 & 1 \end{bmatrix}^{-1} \begin{bmatrix} 3 \\ 9 \\ 27 \\ 81 \end{bmatrix} = \begin{bmatrix} -\frac 16 & \frac 12 & -\frac 12 & \frac 16 \\ \frac 32 & -4 & \frac 72 & -1 \\ -\frac {13}3 & \frac {19}2 & -7 & \frac {11}6 \\ 4 & -6 & 4 & -1 \end{bmatrix} \begin{bmatrix} 3 \\ 9 \\ 27 \\ 81 \end{bmatrix} = \begin{bmatrix} 4 \\ -18 \\ 32 \\ -15 \end{bmatrix}

Therefore, f ( x ) = 4 x 3 18 x 2 + 32 x 15 f(x) = 4x^3 -18x^2 + 32x -15 , f ( 5 ) = 4 ( 125 ) 18 ( 25 ) + 32 ( 5 ) 15 = 195 \implies f(5) = 4(125) -18(25) + 32(5) -15 = \boxed{195} .

Chan Lye Lee
Jul 29, 2018

Let f ( x ) = 3 ( ( x 1 0 ) + 2 ( x 1 1 ) + 2 2 ( x 1 2 ) + 2 3 ( x 1 3 ) ) = 3 ( 1 + 2 ( x 1 ) + 2 ( x 1 ) ( x 2 ) + 4 ( x 1 ) ( x 2 ) ( x 3 ) 3 ) f(x)= 3\left({x-1 \choose 0} +2{x-1 \choose 1}+2^2{x-1 \choose 2}+2^3{x-1 \choose 3}\right) \\ =3\left(1+2\left(x-1\right)+2\left(x-1\right)\left(x-2\right) +\frac{4\left(x-1\right)\left(x-2\right)\left(x-3\right)}{3}\right)

We see that this the degree of f f is 3 and it fulfills and the condition f ( k ) = 3 k f(k)=3^k for k = 1 , 2 , 3 , 4 k=1, 2, 3,4 .

Now f ( 5 ) = 3 ( ( 4 0 ) + 2 ( 4 1 ) + 2 2 ( 4 2 ) + 2 3 ( 4 3 ) ) = 3 ( 3 4 2 4 ) = 195 f(5)= 3\left({4 \choose 0} +2{4 \choose 1}+2^2{4 \choose 2}+2^3{4 \choose 3}\right) =3\left(3^{4}-2^4 \right) = 195 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...